Mammalian mitochondrial DNA replication and mechanisms of deletion formation. (1st November 2020) - Falkenberg, Maria; Gustafsson, Claes M.
Abstract: Mammalian mitochondria contain multiple copies of a circular, double-stranded DNA genome (mtDNA) that codes for subunits of the oxidative phosphorylation machinery. Mutations in mtDNA cause a number of rare, human disorders and are also associated with more common conditions, such as neurodegeneration and biological aging. In this review, we discuss our current understanding of mtDNA replication in mammalian cells and how this process is regulated. We also discuss how deletions can be formed during mtDNA replication.